Low cost marine black box design department of electrical and electronic engineering - Abir, Imtiaz Kalam; Rafique, Rumana; Roy, Sibaji (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2015.